Determinants of aged-friendly urban neighbourhoods in Malaysia / Hanan Mohamed Hassan Elsawahli - Elsawahli, Hanan Mohamed Hassan (2013)
Malaysia is experiencing a rapid increase in its elderly population. According to 2010 census, the number of elderly has risen from 1.4 million in 2000 to 2.1 million in 2010 and is projected to be 3.4 million by 2020. As Malaysia progressed towards becoming a developed and competitive country by 2020, aging population will be a main challenge to planners and policy makers in terms of designing aged-friendly neighbourhoods and providing accessible amenities and services to meet the needs of the elderly. There is a growing interest in aged-friendly neighbourhoods as the neighbourhoods that promotes an active lifestyle among its elderly population, and hence, ensures healthy aging. In Malaysia, active lifestyle among the young elderly is greatly understudied. This study looks at young elderly active lifestyle from the social and physical perspectives. By applying an ecological perspective and building on the WHO framework on ‗age-friendly communities‘ that is based on ‗active aging‘, the study conceptualized aged-friendly neighbourhoods. Data were collected from young elderly aged 60-75 years residing in two neighbourhoods with highest elderly population: TTDI in Kuala Lumpur and Taman Meru in Ipoh. The study adopts mixed methods approach; the qualitative approach involved a phenomenological research to elicit the essence of young elderly active lifestyle experience as lived by 12 young elderly; the quantitative approach involved surveying randomly selected 385 young elderly with regard to their neighbourhood as facilitating/obstructing their active lifestyle. Nine (9) neighbourhood environmental factors were hypothesized to influence young elderly active lifestyle (social interaction, walking, facilitators to walking, physical barriers to walking, convenience, accessibility, permeability, maintenance and safety) as explained by two domains social cohesion and physical activity to identify determinants of aged-friendly neighbourhoods. The qualitative approach included using a simplified version of Hycner‘s process for explication of phenomenological data. For the quantitative approach, the main statistical techniques used for the data analysis were exploratory factor analysis, multiple analyses of variance (MANOVA) and multiple linear regressions. The results of the qualitative data explication showed that the essence of the experience is staying occupied and that staying occupied has the potential to be both physically and socially active. Findings of the quantitative analysis showed that permeability was the salient predictor of young elderly active lifestyle, followed by accessibility and then walking. Therefore, aged-friendly neighbourhoods are those neighbourhoods that are permeable, safe, based on human-scale, pedestrian-friendly, provide access to recreational facilities, have directness of routes, high connectivity and provide many destinations within adequate distance. Triangulating findings from both approaches revealed that aged-friendly neighbourhoods are neighbourhood where their elderly population is both socially and physically active. The results also showed that social activities contributed more to young elderly active lifestyle. This implies that there is a need to understand in more detail the association between subjective and objective neighbourhood environmental measures; and that efforts to curb young elderly active lifestyle should be the responsibility of multi -disciplinary research.